PEMANFAATAN SITUS KOTA TUA PADANGAN KABUPATEN BOJONEGORO SEBAGAI OBJEK PEMBELAJARAN KONTEKSTUAL BERBASIS DIGITAL HISTORY - Muhammad Eko Subagtio (Universitas Negeri Malang, 2022)
The region of Padangan Sub District has local history and an old town building site, but their existence is rarely known among students until general community. This research aimed to find out the historical value of Padangan Old Town site, the relevance of Padangan Old Town site as an object of contextual learning and utilization strategy in digital history based learning. This research employed qualitative descriptive approach. Data collection was carried out through site observation, survey, interview, and exploring some documents in the form of books and relevant journals. The results of this research showed that Padangan sub district has historical attractiveness with the event of Bojonegoro Regency establishment. The first capital city of Bojonegoro Regency was located in Padangan region. Old town side on the other hand showed that Padangan region became a modern civilization with dense population since colonialism era. Some of these heritages could be utilized as history learning objects at Senior High School in material of change and sustainability. The strategy of site utilization in digital history learning could be conducted through four stages namely 1) introduction, 2) observation, 3) discussion, and 4) result. The benefit of digital based contextual learning in Padangan Old Town is to introduce the site presence to students at once disseminating information to public through digital media. The more attractive content information about Padangan Old Town, then the more popular it becomes among the community until it can be made as one of integrated historical tourism destination in Bojonegoro Regency. Wilayah Kecamatan Padangan memiliki sejarah lokal dan situs bangunan kota tua, namun keberadaannya jarang diketahui kalangan pelajar hingga masyarakat umum. Penelitian ini bertujuan untuk mengetahui nilai sejarah situs Kota Tua Padangan, relevansi situs Kota Tua Padangan sebagai objek pembelajaran kontekstual dan strategi pemanfaatan dalam pembelajaran berbasis sejarah digital. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Pengumpulan data dilakukan melalui observasi lapangan, survey, wawancara, dan penggalian beberapa dokumen berupa buku dan jurnal yang relevan. Hasil penelitian menunjukkan bahwa Kecamatan Padangan memiliki daya tarik sejarah dengan peristiwa pembentukan Kabupaten Bojonegoro. Ibukota pertama Kabupaten Bojonegoro terletak di wilayah Padangan. Kota tua di sisi lain menunjukkan bahwa wilayah Padangan menjadi peradaban modern dengan populasi padat sejak era kolonialisme. Beberapa peninggalan tersebut dapat dimanfaatkan sebagai objek pembelajaran sejarah di SMA dalam materi perubahan dan keberlanjutan. Strategi pemanfaatan situs dalam pembelajaran sejarah digital dapat dilakukan melalui empat tahap yaitu 1) pengenalan, 2) observasi, 3) diskusi, dan 4) hasil. Manfaat pembelajaran kontekstual berbasis digital di Kota Lama Padangan adalah untuk memperkenalkan kehadiran situs kepada siswa sekaligus menyebarkan informasi kepada masyarakat melalui media digital. Semakin menarik konten informasi tentang Kota Tua Padangan, maka semakin populer di kalangan masyarakat hingga dapat dijadikan sebagai salah satu destinasi wisata sejarah terpadu di Kabupaten Bojonegoro.